Analysis of the Sales Optimization Model at Neo Café Using the Simplex Method - Indah Chairun Nisa; Carmen Laring Tendean Kalalo; Andhika Albert Kojo; Anugerah Julio Hizkia Kumendong; Gerald Sunantepar Pakala; Riedel Jonathan Langitan; Tessy Angraini Mokodanga (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
Competition in the culinary business sector requires entrepreneurs to manage their resources optimally in order to increase revenue. Neo Cafe, a business operating in the food and beverage industry, faces challenges in determining the optimal combination of menu sales due to limitations in cooking time, service time, and the availability of supporting materials. This study aims to analyze sales optimization at Neo Cafe using Linear Programming with the Simplex method. A quantitative approach is employed by formulating an objective function to maximize revenue, along with constraints that reflect the operational conditions of Neo Cafe. Data were obtained through observation of the production and sales processes of three main menu items: chicken rice, French fries, and butterscotch coffee. The analysis results indicate that the optimal solution is achieved by producing 100 servings of butterscotch coffee per day, while the other menu items are not produced. This production combination generates a maximum daily revenue of IDR 1,800,000 while satisfying all defined constraints. The findings demonstrate that the application of the Simplex method can provide optimal solutions for production and sales decision-making, thereby contributing to improved operational efficiency and increased business revenue.